2021
DOI: 10.1029/2020wr028269
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of Geochemical Elements to Surface Water in the Active Layer of Permafrost in the Russian Arctic

Abstract: Increasing atmospheric temperatures in the Arctic have led to permafrost thawing and vertical downward migration of the active layer into formerly frozen ground during the thawing season (Christiansen et al.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 73 publications
(106 reference statements)
0
10
0
Order By: Relevance
“…Both clusters may be connected to the suprapermafrost waters of the active layer, which are flowing intensely into the thermokarst lakes and rivers. Ji et al (2021) studied elements in permafrost soils and concluded that Mn, Ca, Mg, Al, and Ti showed the highest mobility from soil to suprapermafrost water and further into the ponds and flowing waters. Furthermore, they considered Mn a proxy for predicting the processes occurring in the active layer during summer-autumn thaw.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Both clusters may be connected to the suprapermafrost waters of the active layer, which are flowing intensely into the thermokarst lakes and rivers. Ji et al (2021) studied elements in permafrost soils and concluded that Mn, Ca, Mg, Al, and Ti showed the highest mobility from soil to suprapermafrost water and further into the ponds and flowing waters. Furthermore, they considered Mn a proxy for predicting the processes occurring in the active layer during summer-autumn thaw.…”
Section: Discussionmentioning
confidence: 99%
“…The supply of Cd may be connected to the drainage of mixed suprapermafrost water, which may include atmospheric deposition, and deeper water both. With the active layer deepening, atmospheric pollutants deposited in the past, which have been excluded from the freeze-thaw cycle for a time (Ji et al , 2021), may be remobilised (Edwards et al , 2021;Li et al , 2020;Limet al , 2019;Rubino et al , 2016). The notable increase in Cu, Ni, Pb and Zn concentrations in deep lake waters indicate the likely source of these elements in permafrost thaw, talik water, or enhanced mobility of suprapermafrost water eluting them from soil.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This recognition has motivated research aimed at understanding climate impacts on the sources and sinks of GHG in high latitude inland waters Hutchins et al, 2019;Zolkos et al, 2019;Dean et al, 2020). Of these numerous studies, only a few were conducted in the permafrost-affected rivers, typically at the scale of small watersheds (Denfeld et al, 2013;Serikova et al, 2018;Ji et al, 2020;Castro-Morales et al, 2022). Yet our knowledge of C cycling in so-called middle eight Arctic rivers (Severnaya Dvina, Pechora, Pur, Taz, Khatanga, Olenek, Yana, Indigirka) remains incomplete, preventing accurate quantification and prediction of C source-sink functions and responses to climate change.…”
mentioning
confidence: 99%